Digital maturity of young people – unfolding dependencies between core dimensions and national context as external factor by using a machine-learning approach - Rikke Nyland Christensen; Aqib Siddiqui; Konstantina Valogianni; Arnd Florack; Marco Hubert (Computers in Human Behavior Reports)
In recent years, the interest in determining what constitutes a beneficial use of information and communication technologies (ICTs) has increased, especially with a focus on young people and their digital maturity. To design effective interventions for promoting beneficial digital engagement among young people, it is crucial to understand the interdependency between the core capabilities and digital maturity. Furthermore, how external factors, such as national context, might influence the establishment of an overall index score. Therefore, this paper sets out to validate the digital maturity index and determine the most important dimensions as well as explore if the measurement framework can be considered independent from national context. To do this, we collected data across multiple rounds from 2021 to 2022 (N = 2804) in five European countries (AT, DE, GRE, SLO, DK) and explored it using a novel machine learning approach. We conclude that digital maturity dimensions need further in-depth investigation as some dimensions are subject to more volatility with regard to the context and content of the study. Furthermore, national context plays a crucial role in not only young people's use of ICTs but also in their development of digital maturity.